Mapping Functional Competencies for Strategic Readiness in Public Utilities and Telecommunication Governance: A Case Study of Sarawak Civil Service - Sopian, Bujang; Lee, Jun Choi; Nadri Aetis Heromi, Basmawi; Ade Syaheda Wani, Marzuki (PEGEGOG, 2025)
This study explores a strategic competency mapping initiative within the Ministry of Utilities and Telecommunication (MUT) Sarawak, aimed at enhancing institutional readiness amidst digital transformation and evolving governance challenges. Adopting a qualitative-descriptive design, the study integrates document analysis, focus group discussions (FGDs), and expert panel validation to identify and assess functional competencies across four strategic domains: Digitalization and Data Governance, Utility and Infrastructure Planning, Telecommunication Innovation, and Policy and Regulatory Leadership. The findings reveal substantial competency gaps, particularly in digital literacy,strategic foresight, regulatory agility, and stakeholder engagement. These insights culminate in a context-sensitive competency framework designed to guide workforce development, succession planning, and organizational redesign. The study underscores the importance of aligning competency development with both local governance needs and international standards, providing a replicable model for future-ready capacity building in the public sector.